2013
DOI: 10.1248/bpb.b12-00905
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Profiles and Mechanisms of Orally Administered Coumarin in Mice

Abstract: In the present study, the antinociceptive profiles of coumarin were examined in ICR mice. Coumarin administered orally (from 1 to 10 mg/kg) showed an antinociceptive effect in a dose-dependent manner as measured in the acetic acid-induced writhing test. Duration of antinociceptive action of coumarin maintained at least for 60 min. But, the cumulative response time of nociceptive behaviors induced by a subcutaneous (s.c.) formalin injection, intrathecal (i.t.) substance P (0.7 µg) or glutamate (20 µg) injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Consistent with previous studies , we observed that UVB caused the NHEKs viability loss in a dosage‐ and time‐dependent manner. The medium dosage of UVB irradiation (50 mJ/cm 2 ) was chosen for the following experiments because 100 mJ/cm 2 UVB stimulation led to massive cell death in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies , we observed that UVB caused the NHEKs viability loss in a dosage‐ and time‐dependent manner. The medium dosage of UVB irradiation (50 mJ/cm 2 ) was chosen for the following experiments because 100 mJ/cm 2 UVB stimulation led to massive cell death in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Coumarin is a well-known anticoagulant, and to date, it was not shown to exhibit antidiarrheal activity. On the other hand, recent data suggest that coumarin as well as its derivatives produce antinociceptive effect in the writhing test in mice after oral administration (Park et al 2013 ; Alipour et al 2014 ). This experimental data suggest the contribution of coumarin derivatives in inhibition of abdominal pain in our study.…”
Section: Discussionmentioning
confidence: 99%
“…23 In addition, Park et al 24 demonstrated that coumarin administered subcutaneously (1-10 mg/kg), intracerebroventricularly or intrathecally (10-40 lg) dose-dependently increased the nociceptive threshold in the visceral pain test, but not in models induced by formalin, substance P or glutamate injection. 24 The mechanism of action underlying the analgesic effect of coumarins is not fully understood. However, it is commonly known that LTs, such as cysteinyl LTs LTB 4 , 5-hydroxyeicosatetraenoic acid and 5-oxo-6,8,11,14-eicosatetraenoic acid, play a significant role in inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%